A research method to explore midwives' views of national maternity service reforms. Issue 3 (June 2018) - Roache, Bridget; Kelly, Jennifer
Abstract: Background: Priorities of the National Maternity Services Plan (NMSP) are a significant contrast to current standard hospital maternity service provision. This paper demonstrates the applicability of case study methods to explore the views of midwives during a period of midwifery reform. Aim: This research aims to highlight key findings and insights surrounding recommended changes facing midwives that can be shared with education providers to incorporate strategies into education programs to ensure contemporary midwifery practice. Methods: Exploratory Case Study methodology was employed using ethical processes and designing semi-structured interview questions to explore participants' views. Purposive sampling ensured participants were currently practicing midwives in order to reflect the perspective and intent of this study. Data were analysed and findings presented in categories and subcategories. Results: Case Study methodology enables an in-depth understanding of a phenomenon to be explored within a natural context. The participants of this study formed a single unit of analysis to ensure the research makes a worthwhile contribution to the profession of midwifery. Conclusion: This paper demonstrates that Case Study methodology is a valid research approach to exploring the views of midwives employed in standard care settings during a period of national reform. The rigorous processes and versatility of Case Study methodology ensured a systematic, critical enquiry was undertaken to gain understanding of the views of participants in implementing the NMSP. This understanding is reflective of the real life contexts of midwives to promote understanding and provide a body of knowledge where there is ambiguity and uncertainty.